In Silico Molecular Docking Study Of Antidiabetic Bioactive Compounds From Brotowali (Tinospora cordifolia) Targeting GLUT4 In Type II Diabetes Mellitus - Tarigan, Gita Euaggelion; Dwira, Surya (Indonesian Journal of Medical Chemistry and Bioinformatics, 2026)
Type 2 diabetes mellitus (T2DM) is a global metabolic disorder characterized by insulin resistance and impaired glucose uptake. Despite the availability of pharmacological therapies, limitations such as adverse effects and high costs highlight the need for alternative therapeutic candidates. Tinospora cordifolia has been widely reported to contain bioactive compounds with antidiabetic potential; however, comparative evaluation of their interaction with glucose transporter type 4 (GLUT4) remains limited. This study aimed to identify the most promising bioactive compounds from Tinospora cordifolia targeting GLUT4 using an in silico molecular docking approach, followed by pharmacokinetic and toxicity (ADMET) prediction. Molecular docking was performed using Molegro Virtual Docker with GLUT4 (PDB ID: 7WSM), and six ligands retrieved from the PubChem database. Model validation was conducted using redocking with RMSD < 2 Å. The results demonstrated that hesperetin 7-rhamnoglucoside, verbascoside, and cyanidin 3-O-sambubiosyl 5-O-glucoside exhibited stronger binding affinities than the native ligand, with rerank scores of −137.228, −132.756, and −131.726 kJ/mol, respectively. These compounds formed stable hydrogen bonds with key residues, including Asn176, Gln298/Gln299, and Trp404/Trp428. ADMET analysis indicated that hesperetin 7-rhamnoglucoside and verbascoside possessed more favorable pharmacokinetic profiles with relatively low toxicity risks. In conclusion, hesperetin 7-rhamnoglucoside and verbascoside are identified as the most promising candidates for GLUT4-targeted antidiabetic therapy. These findings provide a computational basis for further experimental validation in the development of novel antidiabetic agents.